A novel method for creatinine adjustment makes the revised Lund–Malmö GFR estimating equation applicable in children. (1st October 2020) - Björk, Jonas; Nyman, Ulf; Delanaye, Pierre; Grubb, Anders; Larsson, Anders; Vranken, Laura; Åkesson, Anna; Pottel, Hans
Abstract: The aim of this study was to establish creatinine growth curves separately for males and females that can be used to adjust childhood levels of serum creatinine to corresponding adult levels. Linear regression with fractional polynomials of age as independent variable was used to construct creatinine growth curves for a reference cohort (n = 83, 157 samples from Belgium and Sweden, age 2–40 years). Adjusted creatinine obtained from the growth curves was used to improve accuracy of estimated glomerular filtration rate (eGFR) based on the Lund–Malmö revised (LMR) equation in children. The LMR equation based on creatinine values adjusted to age 18 years was validated against measured GFR (mGFR) in a separate cohort of 4005 children from four different European countries. Validation metrics included median bias, precision, and accuracy expressed as percentage of estimates within ±30% (P30 ) of mGFR. Remarkable improvements in bias and accuracy were observed; P30 increased from 56% to 74% after creatinine adjustments in children with mGFR <75 mL/min/1.73 m 2 ( n  = 932), while P30 was relatively unchanged (89–90%) at mGFR ≥75 mL/min/1.73 m 2 (n = 3073). The suggested approach with adjusted creatinine makes LMR applicable in children irrespective of their renal function.